CD4+CD25highCD127low/−FoxP3+ Regulatory T Cell Subpopulations in the Bone Marrow and Peripheral Blood of Children with ALL: Brief Report. (29th May 2018) - Niedźwiecki, M.; Budziło, O.; Zieliński, M.; Adamkiewicz-Drożyńska, E.; Maciejka-Kembłowska, L.; Szczepański, T.; Trzonkowski, P.
Abstract : CD4 + CD25 high CD127 low/− FoxP3 + regulatory T cells (Tregs) are currently under extensive investigation in childhood acute lymphoblastic leukemia (ALL) and in other human cancers. Usually, Treg cells maintain the immune cell homeostasis. This small subset of T cells has been, in fact, considered to be involved in the pathogenesis of autoimmune diseases and progression of acute and chronic leukemias. However, whether Treg dysregulation in CLL and ALL plays a key role or it rather represents a simple epiphenomenon is still a matter of debate. Treg cells have been proposed as a prognostic indicator of the clinical course of the disease and might also be used for targeted immune therapy. Our study revealed statistically higher percentage of Treg cells in the bone marrow than in peripheral blood in the group of 42 children with acute lymphoblastic leukemia. By analyzing Treg subpopulations, it was shown that only memory Tregs in contact with leukemic antigens showed statistically significant differences. We noticed a low negative correlation between Treg cells in the bone marrow and the percentage of blasts (R = − 0.36 ) as well as a moderate correlation between Treg cells in the bone marrow and Hb level (R = + 0.41 ) in peripheral blood before therapy. The number of peripheral blood blasts on day 8th correlates negatively (R = − 0.36 ) with Tregs. Furthermore, statistical analysis revealed low negative correlation between the number of Tregs in the bone marrow and the minimal residual disease measured on day 15th, the percentage of blasts in the bone marrow and leukocytosis after 15 days of chemotherapy. These results indicate the influence of Tregs on the final therapeutic effect.